2015
DOI: 10.4236/ijcm.2015.68070
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Early Sexual Initiation and Associated Factors among Preparatory School Students of FaggetaLekoma District, Awi Zone, Northwest Ethiopia, 2015

Abstract: Objective: Early sexual debut increases youth exposure to risky sexual behaviors, STIs including HIV/AIDS, and unsafe abortion. There is study limitation on this speci c issue on the study area. Therefore, this study aimed to determine the prevalence and associated factors of early sexual debut among preparatory school students in Gondar town, North West Ethiopia. Results: From a total of 797 students, 750 respondents complete the questionnaire giving a response rate of 94.1%. About 20.5% with 95%CI (17.6, 23.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
15
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 14 publications
13
15
1
5
Order By: Relevance
“…Decisions of sexual activity often occur simultaneously and substance use increases the probability to initiate sexual activities and had been globally associated with youth risky sexual behaviors (Bizu et al, 2015). In-line with other studies (Abosetugn et al, 2015;Gizaw et al, 2014), this study identify alcohol conception as factor for risky sexual behavior.…”
Section: Factors Associated With Risky Sexual Practicesupporting
confidence: 75%
See 2 more Smart Citations
“…Decisions of sexual activity often occur simultaneously and substance use increases the probability to initiate sexual activities and had been globally associated with youth risky sexual behaviors (Bizu et al, 2015). In-line with other studies (Abosetugn et al, 2015;Gizaw et al, 2014), this study identify alcohol conception as factor for risky sexual behavior.…”
Section: Factors Associated With Risky Sexual Practicesupporting
confidence: 75%
“…Survey conducted in Asia and Africa indicated that, young women and men are under strong social and peer pressures to engaged in risky sexual behavior (Blum et al, 2005) which is the same with studies conducted in Ghana and different parts of Ethiopia (Bizu et al, 2015;Dadi and Teklu, 2014;Dekeke and Sandy, 2014;Oluwatoyin and Oyetunde, 2014;UNAIDS, UNICEF, 2007;Cherie and Berhane, 2012;Shore and Shunu, 2017). This study revealed peer pressure as predictors for risky sexual practice.…”
Section: Factors Associated With Risky Sexual Practicesupporting
confidence: 51%
See 1 more Smart Citation
“…Most studies on youth's sexual initiation have focused on youth between the ages of 15-24. A study conducted in Ethiopia found that youth between the ages of 15-19 years were about four times more likely to start early sexual activities compared to youth between the ages of 20-24 (Bizu, Aderaw, & Kassa, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies conducted in different regions of Ethiopia showed the prevalence of early sexual debut being 64.7% in Debre Markos University [8], 18.40% in Woldiya town [9], 19.0% in Shire-Endessilassie [10], 20.4% in FaggetaLekoma District of Awi Zone [11], 27.6% in Legehida district [12].…”
Section: Introductionmentioning
confidence: 99%